#### Answer

y=-5

#### Work Step by Step

Simplifying
2(5y + 1) + 16 = 4 + 3(y + -7)
Reorder the terms:
2(1 + 5y) + 16 = 4 + 3(y + -7)
(1 * 2 + 5y * 2) + 16 = 4 + 3(y + -7)
(2 + 10y) + 16 = 4 + 3(y + -7)
Reorder the terms:
2 + 16 + 10y = 4 + 3(y + -7)
Combine like terms: 2 + 16 = 18
18 + 10y = 4 + 3(y + -7)
Reorder the terms:
18 + 10y = 4 + 3(-7 + y)
18 + 10y = 4 + (-7 * 3 + y * 3)
18 + 10y = 4 + (-21 + 3y)
Combine like terms: 4 + -21 = -17
18 + 10y = -17 + 3y
Solving
18 + 10y = -17 + 3y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-3y' to each side of the equation.
18 + 10y + -3y = -17 + 3y + -3y
Combine like terms: 10y + -3y = 7y
18 + 7y = -17 + 3y + -3y
Combine like terms: 3y + -3y = 0
18 + 7y = -17 + 0
18 + 7y = -17
Add '-18' to each side of the equation.
18 + -18 + 7y = -17 + -18
Combine like terms: 18 + -18 = 0
0 + 7y = -17 + -18
7y = -17 + -18
Combine like terms: -17 + -18 = -35
7y = -35
Divide each side by '7'.
y = -5
Simplifying
y = -5